Pengaruh Kinerja Keuangan Terhadap Pergerakan Harga Saham Pada Indeks Saham Syariah Indonesia ISSI “Studi Empiris Pada Sektor Mining Yang Listing Di BEI” Periode 2014 – 2018 - Alvin Hidayatullah; Ronny Malavia Mardani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractPurposes of this research is to determine how the effect of financial performance on stock price movements in the Indonesian Islamic Stock Index (ISSI) "Empirical Study in the Sector Mining". The variables used in this research are independent variables: Equity Growth, Net Profit, Return On Equity, Dept Equity Ratio. And the dependent variable: Stock Price Movement. The analysis technique in this research are using explanative analysis, classical assumption test and regression analysis. The population in this study is all Indonesian Islamic Stock Index (ISSI) companies empirical studies in the sector mining. The sample used by author is 10 companies Indonesian Islamic Stock Index in empirical studies on the sector mining with the highest market capitalization. The results of this research indicate that Equity Growth, Net Profit, Return On Equity has a significant positive effect on stock price movements in the sector of the Indonesian Islamic Stock Index mining, while the Dept. Equity Ratio has a significant negative effect on stock price movements in the sector of the Indonesian Islamic Stock Index mining.Keywords : Equity Growth, Net Profit, Return On Equity, Dept Equity Ratio and stock price movements